Curbing Inappropriate Usage of STAT Imaging at a Large Academic Medical Center. Issue 1 (March 2019) - Harvey, H. Benjamin; Alkasab, Tarik K.; Stingley, Preston D.; Shore, Mary T.; Abedi-Tari, Faezeh; Abujudeh, Hani H.; Meyersohn, Nandini M.; Zhao, Jong; Pandharipande, Pari V.; Rosenthal, Daniel I.
Abstract : Purpose: To evaluate a new system for processing and performing inpatient STAT diagnostic imaging with respect to utilization and time-based performance metrics. Materials and Methods: This HIPAA-compliant study had institutional review board approval; informed consent was not required. The radiology information system of a large academic medical center was queried for all inpatient diagnostic imaging exams performed and interpreted from August 1, 2010, to October 31, 2012. Using customized software, data were evaluated based on order priority (non-STAT or STAT) and exam modality with respect to exam volume and time-based performance metrics (time-to-performance and preliminary interpretation time). Data were compared over 3 periods: August 1, 2010, to October 31, 2010 (preimplementation period); November 1, 2010, to October 31, 2011 (year 1 postimplementation); and November 1, 2011, to October 31, 2012 (year 2 postimplementation). Results: In the first year after implementation of the new STAT policy, the percentage of inpatient exams ordered STAT significantly decreased from 22.1% to 5.4% ( P < 0.001). This represented a proportional decrease of 26% (CT), 16% (MRI), 20% (US), and 24% (radiographs) relative to pre-STAT policy levels. The median time-to-performance and median preliminary interpretation time significantly decreased for all modalities after implementation of the policy ( P < 0.05 for all modalities), decreasing by an average of 104 and 162 minutes, respectively. These changes persisted throughout year 2 postimplementation. Conclusion: A new institutional system for handling inpatient STAT diagnostic imaging results in a decreased number of STAT exams ordered and improved time-based performance metrics, thereby increasing workflow efficiency.